(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
This study aims to study the effect of different cooling fluids (pure fluids, Nanofluids and microencapsulated phase change materials suspensions) and the cooling performance of rectangular micro-channel heat sink. Three types of Nanofluids (Al2O3-water, Cu-water,Tio2-water), three types of microencapsulated phase change materials suspensions(MEPCM) are(RT44-water, paraffin wax water, n-octed-water ) and three pure fluids )Water, Oil ,Ethylene Glycol ) were used with constant heat flux(100 W /cm2 ) applied on the base of heat sink. The volumetric concentrations of Nanofluids and MEPCM suspensions (1%, 3%, and 5%) and (100 to 900) is the range of Reynolds number used in this study. The results showed that, using different types of Nanofluids and MEPCM suspensions lead to enhance the cooling performance of the micro channel heat sink (MCHS), since it lead to increase the heat transfer compared with pure fluids. The heat transfer in (MCHS) for MEPCMs is higher than that for Nanofluids. Also, the performance of heat sink increases with increase the concentration of Nanofluids and MEPCMS at certain volumetric concentration